Power, Verticality, and Cinematographic Representation (II): A Reading of «High-Rise» - De Domingo-Soler, Carlos; Urgellés Molina, Alicia (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2023)
This article analyzes the cinematographic representation of power and its dispute through the vertical arrangement of the visual and narrative spaces of the film «High-Rise». We turn to an interdisciplinary approach —audiovisual, political, and meta-legal—, considering the contributions of Michel Foucault and Byung-Chul Han. The research shows that in the film viewed, power is represented though universally accepted spatial conventions, which highlight the social and anthropological dislocations that the characters experience throughout the story.